La expresión musical como vehículo de transformación y cambio socio-político y cómo los nuevos medios han pasado a ser los principales agentes de su difusión: el caso de Calle 13 - Platt, Sarah V. (Diálogos Latinoamericanos, 2014)
From their origin almost ten years ago, the Puerto Rican urban music group, Calle 13, composed by Rene Perez Joglar (Residente) and his half-brother, Eduardo Cabra Martinez (Visitante) has been characterized by a peculiar musical style that is hard to classify into one genre- for it fuses African, Caribbean, and Latin rhythms all in one. This musical proposal has led the group to win a total of nineteen Latin Grammy prizes, and two Grammys- breaking the world record of these awards. However, one more important aspect that characterizes this group is the message they send across to their public. Calle 13´s lyrics are well known for their strong tone of social criticism and irreverence that has caused them to be censored in many Latin American countries, while at the same time their songs have also provoked positive social changes in other nations. The purpose of this research is to analyze how this group has used social media to disseminate their message. In this context, musical expression becomes an agent or vehicle of transformation and social and political change for the public. Moreover, new media becomes indispensable in the speeding up of immediate production. “The content of their lyrics holds the purpose of criticizing and questioning social conditioning, repression against certain subjects, the affirmation of identity, and the establishment of rebellion as a generating mechanism of autonomy and resistance of social beings against attempts of domination that stem from conservative sectors of the population” (Pinedas: 2012). In this paper we will take into account the theory of cultural studies and aesthetics formulated by Andrea Huyssen, which supports central ideas regarding modernism, avantgardism, mass culture and postmodernism. Modernism was originated from a conscious strategy of exclusion, an anguish to become contaminated by a consumerist and oppressive mass culture, and in this context, Calle 13 serves as an example of this formulation. Finally, in this paper we will also analyze the function of media spectacle, the roles assigned by media, and the demands of immediacy of our times. The virtual world we know is enriched by socially constructed messages which are disseminated by new media and the socially charged messages of groups like Calle 13 are nurtured by the immediacy in the transmission and reception of these messages.